2017
DOI: 10.1080/09500693.2017.1299949
|View full text |Cite
|
Sign up to set email alerts
|

Why school students choose and reject science: a study of the factors that students consider when selecting subjects

Abstract: Student study of science at school has been linked to the need to provide a scientifically capable workforce and a scientifically literate society. Educators, scientists and policymakers are concerned that too few students are choosing science for study in their final years of school. How and why students choose and reject certain subjects, including science, at this time is unclear. A Best-Worst Scaling (BWS) survey was completed by 333 Year 10 (age 14-17) students to investigate the relative importance of 21… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
91
1
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(105 citation statements)
references
References 37 publications
7
91
1
6
Order By: Relevance
“…Likewise, students' who reported talking more frequently with a family member about school, for each 1‐point increase, bolstered their attitude score by 0.09, intention by 0.08, behavioral beliefs by 0.07, control beliefs by 0.06, and normative beliefs by 0.15. This interaction is similar to recent findings from Palmer, Burke, and Aubusson (), who reported that students' perceived ability, among other factors, influenced their decision to take elective science coursework in upper secondary school. Their analysis of responses from 333 students, ages 14–17, indicated that parents, peers, and teachers were comparatively less impactful.…”
Section: Findings and Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Likewise, students' who reported talking more frequently with a family member about school, for each 1‐point increase, bolstered their attitude score by 0.09, intention by 0.08, behavioral beliefs by 0.07, control beliefs by 0.06, and normative beliefs by 0.15. This interaction is similar to recent findings from Palmer, Burke, and Aubusson (), who reported that students' perceived ability, among other factors, influenced their decision to take elective science coursework in upper secondary school. Their analysis of responses from 333 students, ages 14–17, indicated that parents, peers, and teachers were comparatively less impactful.…”
Section: Findings and Discussionsupporting
confidence: 89%
“…Yet, from this cross‐sectional perspective, intrinsic predictor variables collected from students were judged to be more effective in explaining variation in their responses to the BRAINS. Group‐level variables relating to the science teacher, ranging from practices to characteristics, have been identified through empirical studies, and remain widely supported as having a tremendous impact on students' enthusiasm for science (e.g., Kolbe & Jorgenson, ; Maltese & Tai, ; Palmer et al, ). Null findings related to these variables in this study may reflect measurement issues associated with the Science Teacher Survey used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In POI, the value component refers to how the person's goals and intentions relate with the attitudes, expectations and values (Krapp, 2002). Students will study science subjects if they need those for their career or future study goals but the importance of science for their everyday life may not be as important (Palmer, Burke & Aubusson, 2017). In addition, individual interest has major influence on students' career choices (Aspden et al, 2015).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…However, students' motivation to learn through school science and their unwillingness to pursue science-related careers has been recognized as a problem. Several influencers that play a role in promoting students' aspirations in science studies and possible science careers have been identified [7,8]. Xiang, Yalan, and Yu (2017) compared the goals of talent cultivation in Chinese and other international CPM schools, determining that schools overseas focus more on cultivating comprehensive qualities in students rather than merely professional knowledge and abilities.…”
Section: Literature Reviewmentioning
confidence: 99%